Worry, Generalized Anxiety Disorder, and Emotion: Evidence from the EEG Gamma Band - Oathes, Desmond J. (2008)
The present study examined EEG gamma (35-70 Hz) spectral power distributions during worry inductions in participants suffering from generalized anxiety disorder (GAD) and in control participants without a history of psychiatric illness. As hypothesized, the EEG gamma band was useful for differentiating worry from baseline and relaxation. During worry induction, GAD patients showed higher levels of gamma activity than control participants in posterior electrode sites that have been previously associated with negative emotion. Gamma fluctuations in these electrode sites were correlated with subjective emotional experience ratings lending additional support to interpretations of negative affect. Following 14 weeks of psychotherapy, the GAD group reported less negative affect with worry inductions and the corresponding gamma sites that previously differentiated the clinical from control groups changed for the GAD patients in the direction of control participants. These findings suggest converging evidence that patients suffering from GAD experience more negative emotion during worry and that the EEG gamma band is useful for monitoring fluctuations in pathological worry expected to follow successful treatment.